The Mitochondrial Routing of the Kv1.3 Channel - Capera, Jesusa; Navarro-Pérez, María; Moen, Anne Stine; Szabó, Ildiko; Felipe, Antonio (Frontiers in Oncology, 2022)
Voltage-gated potassium channels control neuronal excitability and cardiac action potentials. In addition, these proteins are involved in a myriad of cellular processes. The potassium channel Kv1.3 plays an essential role in the immune response mediated by leukocytes. Kv1.3 is functional both at the plasma membrane and the inner mitochondrial membrane. Plasma membrane Kv1.3 mediates cellular activation and proliferation, whereas mitochondrial Kv1.3 participates in cell survival and apoptosis. Therefore, this protein emerges as an important target in cancer therapies. Several forward-traffic motifs target the channel to the plasma membrane in a COPII-dependent manner. However, the mitochondrial import pathway for Kv1.3 is largely unknown. Here, we deciphered the mitochondrial routing of the mitoKv1.3 channel. Kv1.3 uses the TIM23 complex to translocate to the inner mitochondrial membrane. This mechanism is unconventional because the channel is a multimembrane spanning protein without a defined N-terminal presequence. We found that transmembrane domains cooperatively mediate Kv1.3 mitochondrial targeting and identified the cytosolic HSP70/HSP90 chaperone complex as a key regulator of the process. Our results provide insights into the mechanisms mediating the localization of Kv1.3 to mitochondrial membranes, further extending the knowledge of ion channel biogenesis and turnover in mitochondria.